2013
DOI: 10.1136/vr.101907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dimetinden and hydroxyzine/chlorpheniramine in atopic dogs: a randomised, controlled, double‐blinded trial

Abstract: Antihistaminic drugs are commonly used as symptomatic therapy of atopic dermatitis in dogs. Unfortunately, their clinical benefit is largely unsubstantiated. In a double-blinded, placebo-controlled, cross-over trial, the influence of dimetinden and of a combination of chlorpheniramine and hydroxyzine on pruritus and lesions was evaluated in 19 dogs. They were treated with either product or a placebo orally for 14 days, each time followed by a 14-day washout period. Before and after each period, the dogs were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…Although the present study was an open design, the mean percentage reduction in pruritus was higher than that previously reported for the placebo in controlled studies, which ranged between 11% and 20% . Among published reports, the percentage of dogs whose pruritus improved more than 50% at study end ranged from 11% to about 80% . Our result of 35% lies in the middle, being lower than that of prednisolone and higher than antihistamines .…”
Section: Discussioncontrasting
confidence: 85%
“…Although the present study was an open design, the mean percentage reduction in pruritus was higher than that previously reported for the placebo in controlled studies, which ranged between 11% and 20% . Among published reports, the percentage of dogs whose pruritus improved more than 50% at study end ranged from 11% to about 80% . Our result of 35% lies in the middle, being lower than that of prednisolone and higher than antihistamines .…”
Section: Discussioncontrasting
confidence: 85%
“…Additional clinical symptoms, such as pruritus or oedema, can be provoked by MC‐derived mediators, such as histamine . These mediator‐induced effects can often be controlled by histamine receptor (HR)1 and HR2 antagonists . At present, the only curative treatment approach is wide‐margin surgery .…”
Section: Introductionmentioning
confidence: 99%
“…When used in dogs with atopic dermatitis, some dog owners report satisfactory improvement of the clinical signs [13]. In clinical studies, the outcome of treatment with antihistamine is lower: 0–30% of patients are satisfactorily improved [1417]. The very sparse available PK/PD data on antihistamines in the dog make interpretation of these data difficult and it is impossible to evaluate whether the dose produces a pharmacologically relevant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…randomized, blinded and placebo controlled), the results are conflicting [17, 18]. Hsiao et al [18] were unable to demonstrate any difference in pruritus score between cetirizine and control treatments in a study population of 50 dogs whereas Eichenseer et al [17] reported reduction of pruritus after medication with antihistamines (dimethindene or chlorpheniramine/hydroxyzine) in a cross-over study using a study population of 20 dogs. The limited number of dogs included in those studies lowers the statistical power and discrete improvements may have been missed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation